HUBUNGAN RIWAYAT KEHAMILAN, STATUS ASI EKSKLUSIF DAN IMUNISASI DENGAN STUNTING - Aisyah Lahdji; Hema Dewi Anggraheni (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Background: Stunting is one of the global problems that can increase morbidity, mortality, poor development, and infections in children. Some risk factors that escalate stunting incidence are pregnant women, insufficient breastmilk, infection, and the environment.Objective: This study aims to determine the association between pregnancy history, exclusive breastfeeding, and immunisation status with stunting incidence.Methods: This observational study employed a case-control design. The independent variables were pregnancy history, exclusive breastfeeding, and immunisation status. Meanwhile, the dependent variable was stunting incidence. The study subjects were 40 respondents, consisting of 20 respondents diagnosed with stunting and 20 respondents of control.Results: This study revealed an association between a history of low birth weight (p=0.028), too early provision of complementary food in addition to breast milk (p=0.011), no antenatal care (ANC) examination (p=0.000), and exclusive breastfeeding (p=0.028). However, these factors are not significantly different from the immunisation status (p=0.548).Conclusion: This study concluded an association between pregnancy history and exclusive breastfeeding with stunting.